Development and design of a high performance traction machine for the FreedomCar 2020 traction machine targets - Walker, Adam; Galea, Michael; Gerada, David; Gerada, C.; Mebarki, Abdelslam; Brown, Neil (2016)
This paper details the design process of a high performance electrical machine with the objective of achieving US Department of Energy FreedomCar 2020 targets, namely meeting the high speed efficiency requirement without sacrificing performance elsewhere. The FreedomCar targets are detailed, with a short discussion of the challenges involved. All feasible machine topologies are considered, and qualitatively compared in order to identify the best candidate topologies. A set of potential technologies and topologies are evaluated to establish the primary geometry specifications, such as slot pole combination, winding layout and active length. Optimisation methods are then implemented to establish the more detailed geometrical parameters, e.g. tooth width and slot depth. Finally a conclusive design is presented with the finite element simulation results. The design meets all the performance requirements of the targets.